Association between tinnitus and hearing impairment among older adults with age-related hearing loss: a multi-center cross-sectional study - Zhifeng Chen; Zhifeng Chen; Zhifeng Chen; Yan Lu; Yan Lu; Chenyu Chen; Chenyu Chen; Shaolian Lin; Shaolian Lin; Ting Xie; Xiaoyang Luo; Xiaoyang Luo; et al. (Frontiers in Neurology)
ObjectiveThe relationship between tinnitus in the elderly with hearing loss remains elusive. This study aimed to reveal the association between tinnitus and hearing impairment among older adults with age-related hearing loss (ARHL).MethodsThis cross-sectional study was conducted among a population of outpatients diagnosed with ARHL at four medical centers in different regions of China, from June 2020 to June 2023. ARHL patients were divided into two groups based on their self-reported tinnitus: tinnitus and non-tinnitus. Multivariable linear regression models were used to assess the association between tinnitus and hearing impairment in ARHL patients. Subgroup analyses, stratified by gender and age, were performed to further evaluate the association.ResultsA total of 418 older adults with ARHL were included in the study. Compared to the non-tinnitus group, ARHL patients with tinnitus had lower hearing thresholds (β = −5.07; 95% confidence interval (CI) −9.32 to −0.81; p = 0.020). On subgroup analyses stratified by gender and age, the male ARHL patients with tinnitus still had lower hearing thresholds compared to those without tinnitus (β = −6.96; 95% CI −12.70 to 1.22; p = 0.018). In females, tinnitus was not associated with hearing thresholds (β = −3.69; 95% CI −10.11 to 2.74, p = 0.262). There was no association between tinnitus and hearing thresholds in both the age group of ≥70 years (β = −4.31; 95% CI −9.65 to 1.03; p = 0.116) and the age group of <70 years (β = −3.54; 95% CI −9.96 to 2.89; p = 0.282).ConclusionBased on this multi-center cross-sectional study, we reveal that there is no evidence for the assumption that tinnitus may exacerbate hearing loss in the elderly for the first time. On the contrary, tinnitus is associated with better hearing in the male elderly with ARHL. More extensive longitudinal studies are needed to give a comprehensive insight of the present findings and the underlying mechanisms.